2006
DOI: 10.1002/bjs.5212
|View full text |Cite
|
Sign up to set email alerts
|

Local recurrence after curative resection for rectal cancer is associated with anterior position of the tumour

Abstract: Background: Mobilization of rectal cancer can be difficult if the tumour is located anteriorly and may result in a higher incidence of local recurrence. The aim of this study was to determine whether local recurrence and survival following curative resection of rectal cancer were associated with the position of the tumour. Conclusion:Anterior position is an independent negative prognostic factor for both local recurrence and survival after curative resection of rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 36 publications
2
33
0
2
Order By: Relevance
“…This is comparable to the results of Chan et al [29], who found a 5-year relapse-free survival rate of 42% (N1-N2) compared with 85% (N0) in patients after NRC prior to surgery.…”
Section: Discussionsupporting
confidence: 81%
“…This is comparable to the results of Chan et al [29], who found a 5-year relapse-free survival rate of 42% (N1-N2) compared with 85% (N0) in patients after NRC prior to surgery.…”
Section: Discussionsupporting
confidence: 81%
“…The prognostic importance of the circumferential position of the tumour has been reported by different authors, yet with conflicting results (18,19). Chan et al (19) reported that an anterior position is an independent negative prognostic factor for both local recurrence and survival, while Garcia-Granero et al (18) reported that an anterior position did not have prognostic significance. This discrepancy may be due to the definition of tumour location, the inclusion of circumferential tumours and the surgical technique.…”
Section: Discussionmentioning
confidence: 88%
“…The incidence of local recurrence following curative surgery for colorectal cancer, CD, UC, or diverticulitis is high, and has been reported to range from 3.7% to 50% within the first two years (1)(2)(3)(4)(5)21,23). Therefore, it is important to obtain a rapid and exact diagnosis of local recurrence to plan subsequent therapy and possibly surgical reresection of the recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…COLONIC RESECTION with end-to-end-anastomosis is a common procedure in colorectal surgery for patients with colorectal malignancy or chronic inflammatory bowel diseases (1)(2)(3)(4). However, postoperative recurrences at the site of anastomosis with consecutive stricture are frequent.…”
mentioning
confidence: 99%